Measuring performance in agri‐food supply chains: A case study of a Portuguese company - Palhas, J. P.; Ferreira, L. M. D. F.; Vilas-Boas, J.; Almeida, I. D. (Proceedings of 2100 Projects Association Joint Conferences, 2014)
Organizations seek to create value, increase competitiveness, reduce costs, share information and strengthen relationships between the various actors in the chain. In this sense, it is of the utmost importance that tools be developed which define objectives, monitor processes and document the performance of the supply chains. The Performance Measurement Systems (PMS) have come about to aid decision support, bringing together relevant Key Performance Indicators (KPis) which are fundamental for decision makers when deciding the best strategies for increasing supply chain competitiveness. In this study a PMS was developed collating a range of KPIs that seek to help in the continuous improvement of the agri-food supply chain. A case study allowed a PMS model to be designed incorporating the experiences of professionals in the area and subsequent tests to be made of its applicability, its outputs and its usefulness for decision support in a Portuguese plant.